IDENTIFICATION OF PRIORITY LOCATIONS FOR IMPROVEMENT OF DRAINAGE SYSTEM OF CONSERVATION PONDS AND PUMP HOUSES IN FLOOD MANAGEMENT IN JAMBANGAN RAYON SURABAYA CITY - Faris Muhammad, Naufal
The city of Surabaya as a large metropolitan city is faced with major environmental problems as well. The natural landscape of Surabaya City which is in the lowlands and bordering the sea makes the City of Surabaya prone to flooding. In addition, the increasing population density further adds to the level of environmental degradation and increases the vulnerability to flooding in the city of Surabaya. An eco-drainage system was chosen as a solution in dealing with these problems. The drainage system in the city of Surabaya, especially in the Jambangan region, is quite good with the implementation of two eco-drainage methods, namely the conservation pond method and river side polders in one drainage system. With the existence of an eco-drainage system in the Jambangan District, this study aims to evaluate the five existing drainage systems in the Jambangan District and determine priority improvements to increase its function as a flood prevention that still occurs and in dealing with environmental degradation issues. This study uses a Multi-Criteria Decision Analysis (MCDA) approach with the Analytical Hierarchy Process (AHP) method assisted by content analysis in formulating criteria and sub-criteria that influence in determining priorities for improving the drainage system in Jambangan District. From the content analysis, it is formulated that there are three criteria and eight sub-criteria that influence in determining the priority of improving the drainage system in Jambangan District, namely (1) internal system criteria with three sub-criteria, namely pump house, boezem, and drainage channel; (2) the external system criteria with three sub-criteria, namely land problems, waste, and the need for open water storage; (3) the cost criteria with two sub-criteria, namely the losses incurred and the cost of improvement. The results of the research using AHP show that the criteria of the system internals are the most important criteria in determining the priority of improving the drainage system in the Jambangan District. Then the Wonorejo and Rungkut drainage systems has the highest weight as a drainage system that requires improvement in the Jambangan District. This research is expected to be input for the Surabaya City government in determining the criteria that influence the improvement of the drainage system as well as the location of the drainage system which is the priority for improvement resulting from the analysis in this study.